Digital Narratives in Literature: The Art of Presentation - Sumitra Jaiswal (Digital Crossroads: Integrating Humanities, Science and Technology Edition 1, 2025)
In the contemporary era, Digital narratives are the best and most powerful means of acquiring knowledge and amusement. Combining text, images, audio, and video enhances storytelling, making it more immersive and engaging. Earlier the only method of knowing a story was through reading but now digital humanities have brought a transformation in education. It engages the audience through multiple senses. It brings the text closer to reality, provoking the audience to imagine and give a lively experience as a spectator. Though we are not present physically, the special effects make us feel that we are witnesses to what is happening. The advantages of digital narrative are it helps the students develop technical skills and boost their creative thinking. It also enhances their ability to synthesize, analyze, and evaluate information. It fosters independent thinking, problem-solving, and decision-making, allowing learners to question assumptions and consider multiple perspectives. It also fosters the feeling of Empathy an ability to understand and share the feelings of others that promotes collaboration, respect for diverse viewpoints, and the capacity to address social and emotional issues constructively. It makes them Resilient. This paper explores the use of digital narratives in literature as a medium to educate, amuse, and bridge fiction with reality through innovative storytelling. The Lizzie Bennet Diaries, a transmedia adaptation of Pride and Prejudice, this study highlights the potential of digital tools in modernizing classic texts and fostering audience interaction. The analysis also focuses on how digital storytelling can become a stepping stone for creativity and self-expression. Digital narratives in literature as an immersive tool to educate, amuse, develop creativity, and understand virtues. The mythologies like Ramayana, and Mahabharata, the romantic texts like Jane Austin’s “Pride and Prejudice” and Rudyard Kipling’s “The Jungle Book” have made a place apart in the heart of the audience leaving them speculating. My paper will also focus on how Digital online storytelling has become a stepping stone to being creative and vocal. Pride and Prejudice written by Jane Austen is adapted into The Lizzie Bennet Diaries, a transmedia project using YouTube videos, blogs, and social media to modernize the story creating a highly interactive and engaging narrative.